1990
DOI: 10.1111/j.1439-0450.1990.tb01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Enumeration of Reticulocyte in the Peripheral Blood from Canine infected with Babesia gibsoni

Abstract: Summary Peripheral blood samples from dogs infected with Babesia gibsoni were analyzed by a flow cytometer for the percentage of reticulocytes after staining with a membrane‐permeable fluorochrome, thiazole orange. Though thiazole orange has been reported to stain human reticulocytes and Plasmodium‐infected erythrocytes, number of positive cells determined by the flow cytometry did not include that of erythrocytes infected with Babesia gibsoni. Analysis of 51 samples revealed a correlation coefficient of 0.96 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Several authors have confirmed this correlation for samples containing normal or high percentages of reticulocytes (1,3,(5)(6)(7)(8)(9)(10)(11)24,25,27,31,44,45). Davis and Bigelow described the use of fluorescence intensity of the reticulocyte population a s a maturity index to monitor erythropoiesis in recovering bone marrow transplant patients (10).…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…Several authors have confirmed this correlation for samples containing normal or high percentages of reticulocytes (1,3,(5)(6)(7)(8)(9)(10)(11)24,25,27,31,44,45). Davis and Bigelow described the use of fluorescence intensity of the reticulocyte population a s a maturity index to monitor erythropoiesis in recovering bone marrow transplant patients (10).…”
mentioning
confidence: 48%
“…For a single flow cytometric procedure, sources of inaccuracy (misidentification) should be algorithm dependent and due to extraneous cells or debris entering a preset fluorescence window. This aspect of reticulocyte analysis has received some attention recently (23,32,44,45).…”
mentioning
confidence: 99%
“…The sensitivity of flow cytometry for documentation of acute babesial infections parallels that of conventional light microscopy, with a correlation coefficient as high as 0.97 when used in combination with fluorescent nucleic acid staining 107,109,110 . Flow cytometry has also successfully documented chronic infection, with a higher sensitivity than conventional light microscopy, but lower sensitivity than indirect fluorescent antibody (IFA) testing 111 …”
Section: Diagnosismentioning
confidence: 97%